Gene-trait matching among Bifidobacterium dentium strains reveals various glycan metabolism loci including a strain-specific fucosyllactose utilization cluster - Catalano Gonzaga, Ortensia; McKenna, Stephen; O’Neill, Ian; Cotter, Paul D.; McAuliffe, Fionnuala M.; Coffey, Aidan; van Sinderen, Douwe; Bottacini, Francesca (Frontiers in Microbiology, 2025)
In contrast to other human-associated bifidobacteria, Bifidobacterium dentium is commonly classified as an opportunistic pathogen as its presence in the oral cavity has been associated with the development of dental caries. While B. dentium is frequently isolated from the oral cavity of children with caries, recent microbiome investigations and preliminary genomic analyses have suggested that this species is also adapted to colonize the gastrointestinal tract. Understanding the genetic and metabolic adaptations that enable this flexible colonization ability is crucial to clarify its role in human health and disease. To assess B. dentium genomic diversity and metabolic potential, the current study presents analysis and characterization of 10 complete genome sequences from recently isolated B. dentium strains obtained from human fecal samples together with 48 publicly available genome sequences. We investigated genetic loci predicted to be involved in host interaction and carbohydrate utilization in this species by means of comparative genomics, pan-genome analysis, and gene-trait matching. These analyses identified gene clusters involved in the utilization of plant-derived glycans and, for the first time, revealed B. dentium strains capable of utilizing human milk oligosaccharides (HMOs) through a fucosyllactose utilization cluster homologous to the one found in several infant-derived bifidobacterial species. Moreover, additional investigations of strain-specific genetic features highlighted a taxon that is evolved to colonize multiple niches and to compete with other colonizers. These findings challenge the narrow classification of B. dentium as an opportunist and underscore its ecological versatility.